Rancang Bangun Sistem Absensi Berbasis Web Di Madrasah Ibtidaiyah Syamsul Huda Kecamatan Jagakarsa - Dede Handayani; Muhammad AlFathir Shaumi; Hasbi Pandiani; M Berlian Wahyu S (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
In the digital era, the use of information technology in various fields, including education, is essential. Madrasah Ibtidaiyah Syamsul Huda in Jagakarsa District, South Jakarta, faces challenges in recording teacher attendance, which is still done manually, leading to issues such as data inaccuracy and difficulty in recapitulation. This research aims to design and develop a web-based attendance system using PHP, Bootstrap, CSS, HTML, and MySQL. The system is expected to improve the efficiency and accuracy of attendance recording, as well as facilitate real-time access and processing of attendance data. The research methodology includes needs analysis, system design, implementation, testing, and maintenance. The results indicate that the web-based attendance system can provide an effective solution to enhance teacher attendance management at Madrasah Ibtidaiyah Syamsul Huda.